2017
DOI: 10.1128/mbio.01122-17
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Requirement for Robust Regulatory T Cell Responses to Friend Retrovirus Infection

Abstract: Regulatory T cells (Tregs) are immunosuppressive cells of the immune system that control autoimmune reactivity. Tregs also respond during immune reactions to infectious agents in order to limit immunopathological damage from potent effectors such as CD8+ cytolytic T lymphocytes. We have used the Friend virus (FV) model of retroviral infection in mice to investigate how viral infections induce Tregs. During acute FV infection, there is significant activation and expansion of thymus-derived (natural) Tregs that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 72 publications
2
15
0
Order By: Relevance
“…However, the present experiments do not differentiate between direct Treg-mediated effects on CD8 + T cells and indirect effects mediated through APCs. An obvious experiment would be to test B-cell-deficient or -depleted mice during Treg depletion, but we and others have shown that B cells are required for both homeostatic levels and function of Tregs, as well as Treg responses during FV infection (4749). Thus, two-way interactions between Tregs and B cells have potent effects on both cell subsets, and testing them independently in vivo is not yet feasible.…”
Section: Resultsmentioning
confidence: 99%
“…However, the present experiments do not differentiate between direct Treg-mediated effects on CD8 + T cells and indirect effects mediated through APCs. An obvious experiment would be to test B-cell-deficient or -depleted mice during Treg depletion, but we and others have shown that B cells are required for both homeostatic levels and function of Tregs, as well as Treg responses during FV infection (4749). Thus, two-way interactions between Tregs and B cells have potent effects on both cell subsets, and testing them independently in vivo is not yet feasible.…”
Section: Resultsmentioning
confidence: 99%
“…This expansion involves Tregs that do not react with FV antigens but rather self-antigens and is fueled by at least two separate mechanisms. First, natural thymus-derived Tregs, which constitutively express the high affinity IL-2 receptor, are polyclonally activated by IL-2 secreted by F-MuLV-reactive CD4+ T cells and by GITR ligand expressed on activated B cells (Myers et al 2013;Moore et al 2017). Second, thymus-derived Tregs bearing Vβ5 family TCRβ chains specifically react with a retroviral superantigen encoded Downloaded from https://academic.oup.com/femsre/article-abstract/43/5/435/5489187 by guest on 09 June 2020 by endogenous mouse mammary tumor virus 9 (MMTV9) (Myers et al 2013;Joedicke et al 2014a).…”
Section: Cd4+ T Cell Responsesmentioning
confidence: 99%
“…Thus, B cells play paradoxically opposing roles during FV infection. They provide proliferative signals to immunsuppressive Tregs, which slows early virus control through suppression of T cell and B cell responses, and they also produce virus-specific antibodies, which are essential for long-term virus control (Moore et al 2017).…”
Section: B Cell Responses and Antibodiesmentioning
confidence: 99%
“…In FV infections, IL-2 is predominantly produced by FV-specific effector CD4 + helper T cells responding to the infection [ 40 ]. It was recently shown that this IL-2-dependent Treg expansion is also dependent on interactions with B cells [ 48 ]. B cell–dependent Treg signaling occurrs via tumor necrosis factor (TNF) receptor superfamily member 18 (glucocorticoid-induced TNF receptor-related protein [GITR]) ligation with GITR ligand (GITRL) on B cells [ 48 ].…”
Section: Mechanisms Of Treg Expansion And/or Accrual During Retroviramentioning
confidence: 99%
“…It was recently shown that this IL-2-dependent Treg expansion is also dependent on interactions with B cells [ 48 ]. B cell–dependent Treg signaling occurrs via tumor necrosis factor (TNF) receptor superfamily member 18 (glucocorticoid-induced TNF receptor-related protein [GITR]) ligation with GITR ligand (GITRL) on B cells [ 48 ]. Of note, GITR–GITRL interactions are also required to control autoimmunity through regulation of Treg homeostasis [ 49 ].…”
Section: Mechanisms Of Treg Expansion And/or Accrual During Retroviramentioning
confidence: 99%